Robert Plant a life - Rees, Paul K. (Harper Collins, 2013)
"Robert Plant is a living legend. The front man of Led Zeppelin, one of the biggest and most influential rock bands of all time, Plant defined the very notion of what it means to be a rock god. The sheer scale of Led Zeppelin's success is extraordinary. In the United States alone they have sold seventy million records, a figure surpassed only by the Beatles, while "Stairway to Heaven," the band's most famous song, has been played more times on American radio than any other track and is frequently referred to as one of the greatest rock 'n' roll songs ever. But Robert Plant's legacy stretches far beyond Led Zeppelin. This biography is the story of the forces that shaped Plant: from his boyhood in England's Black Country to the ravaging highs and lows of the Zeppelin years; from his relationship with Jimmy Page and John Bonham to the solo career that today, at the age of sixty-two, has him producing some of the most acclaimed work of his career. The author, former editor of Q and Kerrang!, who has in the past interviewed Plant at length, paints a rich, complicated portrait of a man who was only nineteen when he changed the face of rock 'n' roll. This is the definitive story of a musical icon"--Book jacket